PENGARUH LATIHAN SINGLE LEG SPEED HOP TERHADAP POWER OTOT TUNGKAI PADA CLUB FUTSAL PUTRA ABE JEMSI DURI BENGKALIS - M. Ridwan M. Ridwan; Zainur Zainur; Ali Mandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this study is that there is still a lack of goal-shootingability, especially in leg muscle power because the Putra Abe Jemsi Duri futsal club,Bengkalis Regency has never done exercises to improve physical condition, especiallyleg muscle power. To fix this problem, the author provides a form of exercise thatincreases power, especially in the leg muscles, namely single-leg speed hop exercises.The title raised in this study is "The Effect of Single Leg Speed Hop Exercise on LegMuscle Power of Abe Jemsi Duri Putra Futsal Club Athlete, Bengkalis Regency" so thatin the future these athletes can shoot at goal well, and the most important thing afterthis research is to know Is there an increase in the ability to shoot on goal, especially inleg muscle power. The form of this research is (using a one-group pretest-posttestdesign approach) with a population of 17 people at the Putra Abe Jemsi Duri futsalclub, Bengkalis Regency. The instrument used in this study was a standing board jumptest which aims to determine the effect of Single Leg Speed Hop exercise on leg musclepower. After that, the data were processed statistically, to test for normality using theLilliefors test at a significant level of 0.05α. The hypothesis proposed is that there is aneffect of sinlge leg speed hop exercise on leg muscle power in futsal club athletes PutaAbe Jemsi Duri, Bengkalis Regency. Based on the analysis of the normality test of thedata, the results of the pree-test resulted in Lcount of 0.136 and Ltable of 0.206meaning Lcount < Ltable. While the post-test data resulted in Lcount of 0.111 andLtable of 0.206, meaning that Lcount < LTable, then the data was normally distributed.Based on statistical data analysis, there is an average pree-test of 191.41 and anaverage post-test of 223.05. Then based on the analysis of the t-test, the t-test value is10.67 and the t-table is 1.703, so tcount > ttable, then Ho is rejected. and Ha accepted.Thus, it can be concluded that there is an effect of single-leg speed hop exercise on legmuscle power at the Putra Abe Jemsi Duri Futsal club, Bengkalis Regency.Key Words: Single Leg Speed Hop Exercise, Leg Muscle Power